Features of Music That Affect Its Enjoyment following Cochlear Implantation. (23rd August 2013) - Kohlberg, Gavriel D.; Mancuso, Dean; Chari, Divya; Lalwani, Anil K.
Abstract : Objectives: Enjoyment of music remains an elusive goal following cochlear implantation (CI). We assessed the hypothesis that reducing the complexity of music has the potential to enhance the listening experience for the cochlear implantee. Methods: Normal hearing adults (n = 17) were asked to evaluate an original and modified 20‐second piece of country music for its musicality, pleasantness, and naturalness before and after it was processed through CI simulation software. The music was modified by removing the vocals and/or changing the type of musical instruments playing (rhythmic only, melodic only, or combined rhythmic and melodic). Linear regression analysis with analysis of variance was used to assess the impact of music variation on music appreciation. Results: Without CI simulation, music segments that included the vocals, melodic instruments only, or combined rhythmic and melodic instruments sounded more pleasant, natural, and musical. In contrast, music segments processed through the CI simulation sounded more pleasant, natural, and musical when the vocals were removed and when only rhythmic instruments were included (all P values < 0.005). Conclusions: Musical enjoyment with or without CI is influenced by the complexity of the original music. Our study offers preliminary evidence that reduction of music complexity has the potential to make listening more enjoyable for the CI listener. Thus, in addition to improvement in software and hardware, engineering of music specifically for a CI listener may be an alternative means to enhance their listening experience.